A Cross-Sectional Study Describing The Impact Of Oral Health Knowledge On Dental Health Status Among 12-18 Year Old Children Of Lucknow City. (International Journal of Environmental Sciences, 2025)
Introduction: Higher levels of Oral Health Knowledge are associated with better oral hygiene practices and, consequently, improved oral health status. Understanding the relationship is essential for designing effective public health interventions aimed at improving Oral Health knowledge and promoting healthier behaviour. Aims & Objectives: The aim of this study is to assess the level of Oral Health knowledge among Adolescents and to evaluate the oral hygiene practices of Adolescents. Materials & Methods: The study included 462 adolescents from various socioeconomic backgrounds in Lucknow City. Data were collected using a structured questionnaire. The questionnaire was designed to assess Oral Health Literacy, oral hygiene practices, and demographic information. Results: A positive correlation was found between oral health knowledge and oral hygiene practices, indicating that higher knowledge levels contribute to better oral health behaviour. The collected data were analysed using SPSS (Statistical Package for the Social Sciences) software version 25.0. Descriptive statistics were used to summarize the basic characteristics of the study population, including mean, median, standard deviation, and range for continuous variables, and frequencies and percentages for categorical variables. Conclusion: The findings emphasize the need for targeted public health interventions and educational programs that focus on enhancing Oral Health Knowledge, particularly in underserved communities.